Inhibition of breast cancer metastasis suppressor 1 promotes a mesenchymal phenotype in lung epithelial cells that express oncogenic K-RasV12 and loss of p53. - Emily H Hall; Yuan Liu; Aizhen Xiao; Lisa Shock; David L Brautigan; Marty W Mayo; Prasad S Adusumilli; David R Jones (PLoS ONE)
Expression of the breast cancer metastasis suppressor 1 (BRMS1) protein is dramatically reduced in non-small cell lung cancer (NSCLC) cells and in primary human tumors. Although BRMS1 is a known suppressor of metastasis, the mechanisms through which BRMS1 functions to regulate cell migration and invasion in response to specific NSCLC driver mutations are poorly understood. To experimentally address this, we utilized immortalized human bronchial epithelial cells in which p53 was knocked down in the presence of oncogenic K-RasV12 (HBEC3-p53KD-K-RasV12). These genetic alterations are commonly found in NSCLC and are associated with a poor prognosis. To determine the importance of BRMS1 for cytoskeletal function, cell migration and invasion in our model system we stably knocked down BRMS1. Here, we report that loss of BRMS1 in HBEC3-p53KD-K-RasV12 cells results in a dramatic increase in cell migration and invasion compared to controls that expressed BRMS1. Moreover, the loss of BRMS1 resulted in additional morphological changes including F-actin re-distribution, paxillin accumulation at the leading edge of the lamellapodium, and cellular shape changes resembling mesenchymal phenotypes. Importantly, re-expression of BRMS1 restores, in part, cell migration and invasion; however it does not fully reestablish the epithelial phenotype. These finding suggests that loss of BRMS1 results in a permanent, largely irreversible, mesenchymal phenotype associated with increased cell migration and invasion. Collectively, in NSCLC cells without p53 and expression of oncogenic K-Ras our study identifies BRMS1 as a key regulator required to maintain a cellular morphology and cytoskeletal architecture consistent with an epithelial phenotype.